LIBERAL FEMINISM IN ALICE HOFFMAN’S THE RED GARDEN - Hardiyanti, Fanny Nanda; Rohim, Fathur; Sodiq, Machfud Muhamad; Romdlon, Atiq Mohammad; Fanani, Abu (Journal of Language and Literature, 2024)
The purpose of the study was to elaborate the value of liberal feminism conducted by the four women: Hallie, Mary, Emily, and Hannah. The main factor why they did such liberal feminism was that they wanted to do things like what man could do even though they had criticism from the same gender as theirs. Using liberal feminism theory, the researcher found that all the mentioned women namely Hallie, Mary, Emily, and Hannah are in struggle to be in equality as man in any kind of life contribution; Hallie without dependence to her husband and her fight for the famine, Mary with the life freedom and education, Emily with the chance to be educated at school for a study like a man, and Hannah with being unmarried woman in the area of married women.